Potential of livestock manure and agricultural wastes to mitigate the use of firewood for cooking in rural areas. The case of the department of Cordoba (Colombia). (2022) - Sagastume Gutiérrez, Alexis; Mendoza Fandiño, Jorge Mario; Cabello Eras, Juan José; Sofan German, Stiven Javier
Abstract: Modern energy services are essential to replace the extensive use of traditional biomass fuels driving several environmental, health, and social issues affecting the welfare of low-income citizens. Particularly, in Colombia, 11% of the households rely on inefficient firewood cooking systems, while two million people have either intermittent access or no access to electricity. This is particularly important in the department of Cordoba, where an average of 32% of the households relies on firewood for cooking, increasing to 66% of the households in rural areas. Furthermore, 20% of the rural population lack access to electricity. Therefore, this study aims at defining the biogas-based energy potential of the available agricultural and manure wastes in the department. To this end, governmental data is used to estimate the demand for firewood for cooking, the resulting GHG emissions, and the available agricultural and manure wastes. Overall, there are around 1.2 million t of agricultural wastes and 2.2 million t of manure yearly available in the department, representing an energy potential of 6687 TJ. Using 26% of the biogas-based energy potential identified suffices to support the 1334 TJ of biogas needed to replace cooking firewood and to supply the 390 TJ needed for household electricity generation. The use of biogas can reduce GHG emissions to 11% of the emissions resulting from cooking firewood. Polyethylene tubular digesters appear as the most indicated household technology, contrasted to geomembrane tubular digesters that need 2.4 times the initial capital investment while fixed dome digesters need 7.9 times the initial capital investment. Implementing household digesters to support the energy demand for cooking in the department, necessitates a minimum of 18 million USD, while the implementation of 'digester + electric generator' needs between 1.7 and 5.7 million USDdepending on the monthly demand of electricity of 60 kWh or 187 kWh.